Differences in the Approach to Environmental, Social, and Governance (ESG) in Food Sector: A Quantitative Research in Poland - Marzena GANC; Marcin RATAJCZAK; Kamel ROUIBAH; Tomasz FELCZAK (Communications of International Proceedings, 2025)
Sustainable development, encompassing environmental, social, and governance (ESG) aspects, has become a key element in the functioning of enterprises, including those in the food sector. The existing literature lacks in-depth comparative analyses that consider ESG approaches in the context of company size, making this topic particularly important from a theoretical and practical economic perspective. This study aimed to determine the extent of variation in the implementation of ESG principles depending on the size of the analyzed entity. The research was conducted among 26 Polish food companies, involving 117 representatives of management staff. Respondents were divided into three groups based on the size of the company they manage (small, medium, large). A direct interview questionnaire was used, supplemented with the analysis of source documents. The survey was conducted in conjunction with financial statement audit procedures, which allowed for the direct verification of the answers obtained. The Kruskal-Wallis test was used to identify differences between the groups. The results showed that larger companies more frequently implement advanced environmental practices (e.g., use of recycled materials, ecological audits) and exhibit a higher degree of formalization in governance structures (e.g., anti-corruption policies, ESG committees). In the social dimension, differences were less pronounced, possibly due to the existence of standardized labor regulations. All groups of enterprises equally recognized the importance of values such as ethics, transparency, and stakeholder dialogue. The study confirms that ESG is a key element of the business strategy of the examined food companies in Poland, influencing both their image and long-term financial stability. It provides a significant comparative perspective on the implementation of ESG principles depending on company size within the food sector—a field of particularly high social and environmental relevance. The findings fill a gap in the literature by delivering valuable insights into the diversification of ESG practices and identifying areas that require further support and the adaptation of strategies according to enterprise scale.